Disponibilidade e mobilidade de elementos-traço em sistemas aquáticos tropicais - Costa, Henrique Santana (2017)
The complexity of an aquatic system requires understanding the dynamics of its components - both spatially and temporally. The trace elements, being found under different oxidation states (due to their high enrichment factors and low removal rates) are an important environmental stressor. This research aims to determine the availability and mobility of trace elements (Zn), cadmium (Cd), lead (Pb), copper (Cu) and chromium (Cr) between water, sediments and fish in rivers located in the Paraná river basin, in the state of Goiás, Brazil. In order to compare the distribution of these compounds and the dynamics of their flows between fish, sediments and water, data were collected during the dry season (April to September), using descriptive and multivariate statistics data analysis. The analysis of the distribution coefficient (K d ) of the trace elements Cr, Cu and Zn suggests that the water-sediment interaction was influenced by environmental variables: the trace element Cu was influenced by the water temperature; the trace element Zn, in turn, was influenced by the pH of the water. As regards the biotic component, the analysis of the distribution coefficient (K d ) of the trace elements Cr, Cu and Zn (obtained from muscle tissue samples of the fish species collected) suggests that the biomass, migratory habit and basin (hydrology) of the rivers sampled influenced the bioaccumulation of trace elements by fish species. On the other hand, the variables group-trophic, lithology and vegetation cover did not influence the bioaccumulation of trace elements by fish species. It was not observed a relation between the distribution coefficient (K d ) of the trace elements Cr, Cu and Zn in the water-sediment-fish interrelationship, which suggests that the presence/incorporation of these metals occurred independently. There was no indication that geological variables (lithology), anthropic (removal of riparian forest), chemical (pH), hydrological (water velocity) and physical (water temperature) variables influenced the interrelation of Cr, Cu and Zn between analyzed components. The steps involved in this study, as well as the results obtained, characterize the importance of research aimed at a better understanding of the processes that control the availability and mobility of trace elements in aquatic systems.